The model of a potential barrier appearing in a hydrolayer localized in a two-layer porous nanostructure - Bacherikov, Yu.Yu.; Okhrimenko, O.B.; Goroneskul, V.Yu.; Ponomarenko, V.V.; Gilchuk, A.V.; Tytov, S.K.; Lyubchyk, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
A model has been proposed to describe the potential barrier that appears during the interaction of two compacted layers consisting of hydrophilic oxide nanoparticles of different sizes in each layer upon saturation of this structure with adsorbed water. The dependence of the space charge density of the compacted powder material on the density of particles in it has been theoretically calculated. The distribution of the potential over the thickness of the contact between two layers consisting of nanoparticles with different sizes has been obtained. Запропоновано модель потенціального бар’єра, який виникає у процесі взаємодії двох компактованих шарів, які складаються з наночастинок гідрофільного оксиду різного розміру у кожному шарі, при насиченні такої структури адсорбованою водою. Теоретично розраховано залежність густини об’ємного заряду пресованого порошкового матеріалу від щільності частинок у ньому. Отримано розподіл потенціалу по товщині контакту двох шарів, які складаються з наночастинок різного розміру.